In Situ Infrared Study of the Electrooxidation of Ethanol and Acetaldehyde in Acid Electrolyte. Issue 7 (18th May 2016) - Torrero, Jorge; Pérez‐Alonso, Francisco J.; Peña, Miguel A.; Domínguez, Carlota; Al‐Youbi, Abdulrahman O.; Al‐Thabaiti, Shaeel A.; Basahel, Sulaiman N.; Alshehri, Abdulmohsen A.; Rojas, Sergio
Abstract: The electrooxidation of ethanol and acetaldehyde on Pt/C has been studied by using in situ IR spectroscopy. To identify the species formed during the electrooxidation reactions accurately, the IR spectra were collected in both HClO4 /H2 O and HClO4 /D2 O electrolytes. The results shown herein reveal that ethanol adsorbs on Pt at low potentials in a series of dehydrogenative steps that lead to η2 ‐acetaldehyde prior to the scission of the C−C bond, which takes place at potentials higher than 150 mV. At potentials of approximately 220 mV, the Pt surface is fully covered by COad (and C1, ad ) species, which thus impede further ethanol adsorption. At higher potentials, when OHad species are nucleated, COad is oxidized to CO2, which releases Pt sites for further ethanol adsorption and oxidation. However, due to the presence of OHad species, ethanol oxidation to acetic acid is the preferred reaction pathway. In contrast, the C−C bond of acetaldehyde is broken at 50 mV, which leads to the formation of a full monolayer of CO and CH x adsorbed species on Pt. The IR spectra collected in an electrolyte that contained D2 O show no evidence for the formation of acetyl species prior to the scission of the C−C bond. Abstract : Potential differences : At low potentials, the dehydrogenative adsorption of ethanol on Pt leads to the formation of η2 ‐acetaldehyde prior to the formation of COad (see figure).